2010
DOI: 10.1109/lpt.2010.2049834
|View full text |Cite
|
Sign up to set email alerts
|

Scalability of Optical Interconnects Based on Microring Resonators

Abstract: This paper investigates the use of optical microring resonators as switching elements in large optical interconnection fabrics. We introduce a simple physical-layer model to assess scalability in crossbar-and Benes-based architectures. We also propose a new dilated switching element that improves scalability to build fabrics of several Tbps of aggregate capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Furthermore, the use of smaller bitrates leads to a slightly larger scalability, due to the larger granularity in the use of the spectrum. Table 1(b) shows the final TTx tuning range w in THz needed to support the aggregated capacities reported in Table 1(a), when a maximum ACC X = 50 is allowed [4]. Dashes are placed where the resulting w was higher than 60 THz, a value today unreachable by TTxs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the use of smaller bitrates leads to a slightly larger scalability, due to the larger granularity in the use of the spectrum. Table 1(b) shows the final TTx tuning range w in THz needed to support the aggregated capacities reported in Table 1(a), when a maximum ACC X = 50 is allowed [4]. Dashes are placed where the resulting w was higher than 60 THz, a value today unreachable by TTxs.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in [4] we showed that a 50 × 50 MRR-based crossbar is feasible using a single optical channel (X = 50). Furthermore, the above proposed ACC reducing strategies, can enhance the physical scalability.…”
Section: Feasibility Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have been conducted to estimate the maximal scalability of ring based switches, considering different cascading architectures [8,9]. However, to the best of our knowledge, analyses conducted so far model the deleterious effects of the switches based on extrapolations from lab-measurements of single devices.…”
Section: Introductionmentioning
confidence: 99%
“…Both pure all-optical and hybrid electro-optic solutions have been investigated [2] [3]. On the hybrid front, various switch architectures have been investigated which either use electrically driven phase shifters [4], semiconductor optical amplifiers (SOAs) [5] or microring resonators [6]. Effort has also been put into building all-optical systems.…”
Section: Introductionmentioning
confidence: 99%